GrapeTree: visualization of core genomic relationships among 100,000 bacterial pathogens - Zhou, Zhemin; Alikhan, Nabil-Fareed; Sergeant, Martin J; Luhmann, Nina; Vaz, Cátia; Francisco, Alexandre P; Carriço, João André; Achtman, Mark (Genome research, 2018)
Current methods struggle to reconstruct and visualize the genomic relationships of large numbers of bacterial genomes. GrapeTree facilitates the analyses of large numbers of allelic profiles by a static "GrapeTree Layout" algorithm that supports interactive visualizations of large trees within a web browser window. GrapeTree also implements a novel minimum spanning tree algorithm (MSTree V2) to reconstruct genetic relationships despite high levels of missing data. GrapeTree is a stand-alone package for investigating phylogenetic trees plus associated metadata and is also integrated into EnteroBase to facilitate cutting edge navigation of genomic relationships among bacterial pathogens.